“Turn-on” fluorescence probe integrated polymer nanoparticles for sensing biological thiol molecules - Li, Menghuan (2015)
A “turn-on” thiol-responsive fluorescence probe was synthesized and integrated into polymeric nanoparticles for sensing intracellular thiols. There is a photo-induced electron transfer process in the off state of the probe, and this process is terminated upon the reaction with thiol compounds. Configuration interaction singles (CIS) calculation was performed to confirm the mechanism of this process. A series of sensing studies were carried out, showing that the probe-integrated nanoparticles were highly selective towards biological thiol compounds over non-thiolated amino acids. Kinetic studies were also performed to investigate the relative reaction rate between the probe and the thiolated amino acids. Subsequently, the Gibbs free energy of the reactions was explored by means of the electrochemical method. Finally, the detection system was employed for sensing intracellular thiols in cancer cells, and the sensing selectivity could be further enhanced with the use of a cancer cell-targeting ligand in the nanoparticles. This development paves a path for the sensing and detection of biological thiols, serving as a potential diagnostic tool in the future.